Pelatihan Interaktif Penggunaan Aplikasi Digital Qris Sebagai Alat Pembayaran Pada UMKM Di Desa Kraton, Kecamatan Krian, Kabupaten Sidoarjo - Munawaroh, Siti (Welfare : Jurnal Pengabdian Masyarakat, 2023)
This service program aims to empower micro, small, and medium enterprises (MSMEs) in Kraton Village by introducing and implementing payment methods using QR codes. This method is considered effective for modernizing payment systems and increasing transaction efficiency in MSME businesses. In its implementation, this program adopts an interactive training method that directly involves MSME owners. They are given an in-depth understanding of the use of QR code technology in their daily transactions. The results of this implementation show significant improvements in transaction efficiency, with reduced payment processing times and a reduced risk of administrative errors. This service program has succeeded in empowering MSMEs in Kraton Village by giving them access to modern payment technology. By adopting QR codes, MSMEs can expand their market reach and increase their competitiveness in the digital economy era. The success of this program is proof that empowerment through QR Code payment technology is a positive step in advancing MSMEs in the local area.